AsiaPacifiQueer : rethinking genders and sexualities - Martin, Fran, 1971-; McLelland, Mark J., 1966-2020; Yu, Audrey (University of Illinois Press, 2008)
"A multidisciplinary, multicultural reassessment of gender and sexuality in the Asian Pacific"--Publisher's description